2022
DOI: 10.1108/tr-03-2022-0108
|View full text |Cite
|
Sign up to set email alerts
|

Customer responses to airline companies' service failure and recovery strategies: the moderating role of service failure habit

Abstract: Purpose The purpose of this study is to investigate the perceived severity of service failure (PSSF) and service recovery strategies (SRSs) as antecedents of customer forgiveness (CF), customer reconciliation, negative word-of-mouth and re-patronage intention as outcomes across two Middle Eastern countries: Egypt and Oman. Design/methodology/approach A quantitative technique was used, using a questionnaire, to collect data from customers of the national airline companies of Egypt and Oman. The perspectives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Thus, H6 was not supported. As mentioned by Anagnostopoulou et al (2020), Ciasullo et al (2021) and Elbaz et al (2022), customer satisfaction was achieved not only in terms of response timing or the volume of online reviews but also the valence of responses. Our analysis showed that H6 was not supported because most online reviews were negative, and regardless of the number of reviews, negative reviews had a similar negative impact on hotels.…”
Section: Effect Of Public Response On Abnormal Returns and Cumulative...mentioning
confidence: 83%
“…Thus, H6 was not supported. As mentioned by Anagnostopoulou et al (2020), Ciasullo et al (2021) and Elbaz et al (2022), customer satisfaction was achieved not only in terms of response timing or the volume of online reviews but also the valence of responses. Our analysis showed that H6 was not supported because most online reviews were negative, and regardless of the number of reviews, negative reviews had a similar negative impact on hotels.…”
Section: Effect Of Public Response On Abnormal Returns and Cumulative...mentioning
confidence: 83%
“…Wei and Kim (2021) also emphasised that airlines should prioritise effective communication during the crisis. Therefore, maintaining clear communication with customers, preventing service failure and minimising customer complaints will help increase passenger loyalty (Elbaz et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The managers may also use the findings in understanding the conceptual framework, its fundamentals, metamorphisms and advancements. This will facilitate the managers to develop better marketing strategies for improved customer retention (Adzoyi et al ., 2021; Stauss et al ., 2001) and reduced service failure (Chen et al ., 2022; Elbaz et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%